Effects of androgen and oestrogen on IGF pathways controlling phallus growth. Issue 1 (January 2019) - Chen, Yu; Yu, Hongshi; Pask, Andrew J; Fujiyama, Asao; Suzuki, Yutaka; Sugano, Sumio; Shaw, Geoff; Renfree, Marilyn B
Abstract : The development of the mammalian phallus involves hormone-dependent mesenchymal–epithelial signalling mechanisms that contribute to urethral closure and regulation of phallus elongation and growth. In marsupials, most differentiation and growth of the phallus occurs post-natally, making them amenable to direct hormone treatment. Expression of IGFs, FGFs, EFNB2, MAFB, DLX5 and AP-1 mRNAs in the phallus at day 50 post-partum (pp) were altered after treatment of tammar wallaby young from day 20 to 40 pp with androgen, oestrogen or after castration at day 25 pp. However, the most interesting changes occurred in the IGF pathway genes. Androgen treatment upregulated IGF1 in female phalluses and oestrogen treatment upregulated IGF1 in male phalluses, but it was downregulated by castration. IGFBP3 was higher in female phalluses and downregulated by androgen. IGF1 expression was higher in all untreated male than in female phalluses from day 50 to 150 pp, but IGFBP3 had the reverse pattern. At day 90 pp, when urethral closure in males is progressing and male phallus growth is accelerating. IGF1 and PCNA protein were only detected in the male urorectal septum, suggesting for the first time that closure and elongation may involve IGF1 activation of cell proliferation specifically in male phalluses. These effects of sex steroids on gene expression and on the IGF1 signalling pathway in particular, suggest that the developing phallus may be especially susceptible to perturbation by exogenous hormones.